Utilization of Digital History as A History Learning Media during Covid-19 Pandemic (Case Study on SMA Negeri 8 Yogyakarta) - Zulkarnain, Zulkarnain (History Department, Semarang State University and Historian Society of Indonesia, 2022)
The implementation of digital history media in history learning during the COVID-19 pandemic is currently very necessary. By utilizing the existing internet learning media, teaching and learning activities will still be able to be carried out even from their respective homes. This is not only to break the chain of spread of COVID-19 but also to prepare students of SMA Negeri 8 Yogyakarta to gace the upcoming discourse of society 5.0. This research was conducted using a qualitative method and a phenomenological approach. The results of this study indicate that in general SMA N 8 Yogyakarta and it is educational apparatus have implemented this digital history, starting from workshops for subject teacher to map learning strategies, implementation, controlling and evaluation well. Apart from the advantages, disadvantages and various obstacles faced, this digital history media has proven to be able to be an alternative for appropriate teaching and learning activities during the pandemic.Penerapan media sejarah digital dalam pembelajaran sejarah di masa pandemi COVID-19 saat ini sangat diperlukan. Dengan memanfaatkan media pembelajaran internet yang ada, kegiatan belajar mengajar akan tetap dapat dilaksanakan walaupun dari rumah masing-masing. Hal ini tidak hanya untuk memutus mata rantai penyebaran COVID-19 tetapi juga untuk mempersiapkan siswa SMA Negeri 8 Yogyakarta menghadapi wacana masyarakat 5.0 mendatang. Penelitian ini dilakukan dengan menggunakan metode kualitatif dan pendekatan fenomenologis. Hasil penelitian ini menunjukkan bahwa secara umum SMA N 8 Yogyakarta beserta aparatur pendidikannya telah menerapkan sejarah digital ini, mulai dari workshop untuk guru mata pelajaran hingga memetakan strategi pembelajaran, pelaksanaan, pengendalian dan evaluasi dengan baik. Terlepas dari kelebihan, kekurangan dan berbagai kendala yang dihadapi, media sejarah digital ini terbukti mampu menjadi alternatif kegiatan belajar mengajar yang tepat di masa pandemi.Cite this article: Zulkarnain. (2022). Utilization of Digital History as A History Learning Media during Covid-19 Pandemic (Case Study on SMA Negeri 8 Yogyakarta). Paramita: Historical Studies Journal, 32(1), 149-158. http://dx.doi.org/10.15294/paramita.v32i1.33248